Comparative Evaluation of Plaque Inhibitory and Antimicrobial Efficacy of Probiotic and Chlorhexidine Oral Rinses in Orthodontic Patients: A Randomized Clinical Trial - Shreya Shruthi Shah; Supriya Nambiar; Deepa Kamath; Ethel Suman; Bhaskaran Unnikrishnan; Asavari Desai; Sanchit Mahajan; Kushan Kishore Dhawan (International Journal of Dentistry)
Background. Antimicrobial agents serve as an effective adjunct in plaque control, and chlorhexidine has been the gold standard. However, the philosophy that natural agents are better for children's oral health is on the rise. Probiotic technology represents a breakthrough approach to maintain oral health by utilizing natural beneficial bacteria commonly found in healthy mouths. Aim and Objective. To compare efficacy of probiotic and chlorhexidine oral rinses in orthodontic patients. Materials and Methods. 30 healthy patients undergoing fixed orthodontic treatment were randomly selected for the study by block randomization and allocation concealment and were divided into three groups: group a, 0.2% chlorhexidine mouthwash; group b, probiotic mouthwash; and group c, a control group. Results. Probiotic and chlorhexidine groups had significantly decreased plaque indices as compared to the control group. However, greater improvement was seen in the gingival indices than plaque indices with better results in the probiotic group than the chlorhexidine group. No statistical significance was observed in the streptococcus count of probiotic and chlorhexidine groups at the end of the intervention period. Conclusion. The comparison of probiotics to chlorhexidine has proven that probiotics are as effective as chlorhexidine as an adjunctive chemical plaque control agent.